2018
DOI: 10.1002/ajs4.35
|View full text |Cite
|
Sign up to set email alerts
|

Street‐level discretion, emotional labour and welfare frontline staff at the Australian employment service providers

Abstract: Despite the current controversial debates about discretion in public bureaucracies in general, and in welfare agencies in particular, the current literature on street-level bureaucracy mainly assumes that discretion is a distinctive feature of the daily work of public servants. Nonetheless, a pertinent question has not specifically been asked in this literature, that is, given the context of privatisation and increased welfare conditionality in the welfare sector that are seriously challenging welfare frontlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Qualitative participants aligning with narrative two and three seemed more receptive to the support they felt was provided to them within their engagement with DES. As highlighted in these narratives and other research, perhaps a greater individual need for support was matched with more highly-skilled workers that could work within DES to develop more positive worker-participant alliances [54,[72][73][74]. Such DES workers were described in ways that most resonated with recovery-orientated practice, in that they were reported to take the time to develop trusting relationships, and listen and respect the hopes and aspirations as well as the fears and concerns of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative participants aligning with narrative two and three seemed more receptive to the support they felt was provided to them within their engagement with DES. As highlighted in these narratives and other research, perhaps a greater individual need for support was matched with more highly-skilled workers that could work within DES to develop more positive worker-participant alliances [54,[72][73][74]. Such DES workers were described in ways that most resonated with recovery-orientated practice, in that they were reported to take the time to develop trusting relationships, and listen and respect the hopes and aspirations as well as the fears and concerns of participants.…”
Section: Discussionmentioning
confidence: 99%
“…SLBs must also feel confident that their clients will not behave opportunistically and try to bend policy to benefit themselves (Chen et al 2014). These concerns may be exacerbated when they meet clients whom they regard as manipulative (Maynard-Moody and Leland 2000), aggressive (Nguyen and Velayutham 2018), or untrustworthy (Raaphorst and Van de Walle 2018).…”
Section: Trust In the Context Of Street-level Workmentioning
confidence: 99%
“…While some of the studies have suggested that views about Australian employment services are not always negative and that frontline workers will attempt to provide extra support for their clients even despite organisational imperatives (e.g. Nguyen & Velayutham 2018; Nguyen 2019), many have suggested that an overemphasis on compliance has a damaging effect on unemployed workers. For example, Marston and McDonald’s (2008) findings from their longitudinal study of Australian unemployed workers suggest that unemployed workers become demotivated because employment services are ineffective rather than employment services being ineffective because unemployed workers are demotivated.…”
Section: Introductionmentioning
confidence: 99%